Salmon Creek Glacier, Alaska scale 1:5,000 / prepared by James B. Case at the Institute of Geodesy, Photogrammetry, and Cartography, the Ohio State University under the American Geographical Society's IGY Project 4.11 - Ohio State University (American Geographical Society of New York, 1959)
Blueline print.; Relief shown by contours and spot heights.; Folded into "IGY Project 4.11 report no. 9 Map of the Salmon Creek Glacier, Kenai Mountains, Alaska" by James B. Case, January 1959. Color 1:10,000